2008
DOI: 10.1016/s0140-6736(08)60886-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural strategies to reduce HIV transmission: how to make them work better

Abstract: This paper makes five key points. First is that the aggregate effect of radical and sustained behavioural changes in a sufficient number of individuals potentially at risk is needed for successful reductions in HIV transmission. Second, combination prevention is essential since HIV prevention is neither simple nor simplistic. Reductions in HIV transmission need widespread and sustained efforts, and a mix of communication channels to disseminate messages to motivate people to engage in a range of options to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
524
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(549 citation statements)
references
References 88 publications
9
524
0
8
Order By: Relevance
“…This result is also in line with Coates, Richter, and Caceres (2008) who confirmed that behavior modification is best achieved by small peer group sessions and community based approaches rather than large scale campaigns, which produce marginal changes that are difficult to sustain. Zeelen, Wijbenga, Vintges, and Jong (2010) reported adoption of old traditions of storytelling and youth literature as a new methods of AIDS education among South African youths based on findings that mass education focused approaches are not inclusive enough to break with cultural stereotypes.…”
Section: Discussionsupporting
confidence: 87%
“…This result is also in line with Coates, Richter, and Caceres (2008) who confirmed that behavior modification is best achieved by small peer group sessions and community based approaches rather than large scale campaigns, which produce marginal changes that are difficult to sustain. Zeelen, Wijbenga, Vintges, and Jong (2010) reported adoption of old traditions of storytelling and youth literature as a new methods of AIDS education among South African youths based on findings that mass education focused approaches are not inclusive enough to break with cultural stereotypes.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, Coates et al suggested that a network-based intervention may be an innovative approach for use among groups of stigmatized and vulnerable people, like MSM, who are systematically alienated from health services [7]. This may involve gaining access to the "secret" sexual network by identifying key individuals and training them for the purpose of disseminating HIV-protective strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence underpins the assertion of Coates et al that delaying the age at which the person had his first sexual intercourse would be effective in reducing HIV transmission [7]. In accordance with that evidence, the participants' answers were first averaged, and then each man's answer was dichotomized as below or above that average age; an above-average age at sexual debut was treated as indicating a protective factor.…”
Section: Resilience Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Coates et al [29] point out, social justice is necessary to optimize public health efforts. Lehman and colleagues conclude their report by suggesting that state legislatures reconsider HIV criminalization law through the lens of the current science of HIV transmission and treatment.…”
Section: Social Justicementioning
confidence: 99%